Pengaruh Penambahan EM-4 dan Urea dalam Campuran Bahan Kering dan Limbah Cair Tempe Terhadap Produksi dan Nilai Kalor Biogas pada Digester - Saputro, Harjo Dwi; , Nur Aklis, S.T., M.Eng (2016)
Biogas is the result of fermentation of organic material by bacteria anaerobic. It produces gas which are mostly methane (CH4) and carbon dioxide (CO2). The purpose of this study are 1) to design a tool for making biogas (digeseter) on a small scale batch type, 2) to determine the effect of urea and EM-4 on a mixture of tempe liquid waste and rice husks with a ratio of 4: 1which is optimal on biogas, and 3) to know how much the heat value which is produced. Variations of the mixture in this test are the addition of 0% Urea and EM -4, 1% urea, 1% EM-4, and 1% urea + EM-4. This test is begun by designing the digester tube, and then performing the installation assembly digester tube which its size 120 L and other components. After that, the next step is checking process on all components of the installation prior to the tests. The next step is charging process of raw materials such as tempe liquid waste and rice husks based on predetermined composition. It is also added by supporting material for decaying. Those are Urea and EM-4. The fermentation process is carried out for 30 days. It is stirred the contents of raw materials for 10 minutes twice a day. The result shows that the highest biogas production is 0.0223 kg which is produced by mixture with addition of 1% urea + EM-4, while the lowest biogas production is 0.0139 kg which is produced by mixtures without any addition of urea and EM-4. The highest heat value of biogas which is produced by mixture with addition of 1% urea + EM-4 is 663.19 Kj. While, the smallest heat value which is produced by mixture without addition of urea and EM-4 is 364.52 Kj. It can be concluded that the most optimal mixture is 1% Urea + EM-4 at 80% on tempe liquid waste and 20% on rice husks. Keywords: biogas, digester tube, tempe liquid waste, rice husks, urea, EM-4